Pengaruh work-life balance dan perceived organizational support terhadap employee engagement pada BPJS Ketenagakerjaan - Addin Eka Septiani; Agus Frianto (UNESA In Collaboration With APSMBI (Aliansi Program Studi dan Bisnis Indonesia), 2023)
This study examines the effect of work-life balance and perceived organisational support on employee engagement. The sampling used a saturated sample technique with 34 respondents from employment insurance service providers and a Multiple Linear Regression data analysis technique with SPSS software version 25. The results showed that work-life balance has no significant impact on employee engagement. Work-life balance conditions in employees are not a vital factor in increasing employee engagement with the company. Whereas when viewed on variables, perceived organisational support significantly and positively impacts employee engagement. The higher the perceived corporate support in employees, the more employee engagement with the company. Furthermore, the test results prove that work-life balance and perceived organisational support significantly and positively impact employee engagement. Based on research, companies need to consider how perceived organisational support is owned by their employees, such as holding evaluations of each division, monthly meetings, and the best employee of the month program so that later it can increase employee engagement with the company.